Assessment of Colour Blindness and Erythrocyte G6PD Enzyme Status among the School Children of Dhaka City - Yasmin, Ayesha; Janan, Nasima; Akhter, Rezina (Journal of Bangladesh Society of Physiologist, 2010)
Background: Visual impairment due to colour blindness is an unusual suffering of the school children. It may be associated with erythrocyte G6PD enzyme deficiency. Objective: To find out defective vision due to colour blindness in apparently healthy school children and to measure erythrocyte G6PD enzyme level among them. Methods: This cross sectional study was carried out in the Department of Physiology, SSMC from 1st July 2007 to 31st June 2008. Five hundred (500) apparently healthy school children of old Dhaka, age ranged from 6 to 12 years irrespective of gender and race was selected as study population. Colour vision test was done by Ishihara's test. Erythrocyte G6PD enzyme was measured among the colour blind children. All the results were compared to that of children with normal colour vision. Results: Five male children were detected to have partial red-green type of colour blindness. The percentage of colour blindness was statistically not significant (p>0.05) when compared to that of children with normal colour vision. Mean erythrocyte G6PD enzyme level of colour blind children was significantly lower (p<0.05) compared to that of children with normal colour vision. Presence of G6PD enzyme deficiency among the colour blind children did not show any clinical abnormalities might be due to different non symptomatic G6PD variants. Conclusion: Visual defect due to colour which blindness particularly red-green type might be present in apparently healthy school children associated with erythrocyte G6PD enzyme deficiency. Key words: Colour blindness; Erythrocyte G6PD enzyme. DOI: 10.3329/jbsp.v4i2.4175 J Bangladesh Soc Physiol. 2009 Dec;4(2): 64-70